Revisión bibliográfica de la Prevalencia de maloclusiones dentomaxilares y factores asociados en los trabajos de grado de la Universidad Antonio Nariño Sede Ibagué en los años 2014 -2020. - Díaz Girón, Florenia (Universidad Antonio Nariño, 2021)
Malocclusion is defined as an inadequate position of bony bases, such as the mandible and maxilla; it can only occur dentally, but they can be associated with combined malocclusions, being both bone and dental alterations. These are the most prevalent disease after dental caries and periodontal disease. It is of multifactorial origin and among the causes, the presence of oral habits can be found, the diet that the population eats should be observed, little stimulation of maxillomandibular growth, muscle development, and discrepancies in the size and shape of the jaws